EFFECTIVE SCHOOL MODEL; MALAYSIAN PERSPECTIVE - MUHAMMAD FAIZAL A GHANI; SAEDAH SIRAJ (Al Qalam, 2010)
The excellence education has become the primary concern for achievement to compete in this global village. Since the technological and vocational higher education became one of the essential elements in the educational road map, students are expected to be more skillful than the one of regular university. This stutfy reviews the development of effective learning systems and examines the relationship between employability and effective learning systems from students' perception. The results found that the model indicates a highly acceptable fit between the model and data. Also, there exists significant direct effect between employability and effective learning systems. Key words: school model, malaysian.